FACTORS OF MUTUAL AGGRAVATION OF MULTIPLE CHRONIC FOCI OF INFECTION AND GENERALIZED PERIODONTITIS - I. A. Gorbachevа; L. Y. Orehova; Y. A. Sycheva; T. N. Chudinova; O. V. Mikhailova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. The Inflammatory Diseases of the Parodont (IDP) of generalized character are closely connected petrogenetically with internal pathology and are a serious factor of its burdening, forming a negative comorbidity. Pro-inflammatory reactions and metabolic shifts, such as oxidizing stress, violation of regulatory participation of the vital minerals at an imbalance of their distribution in biological environments are the inflammatory mechanisms uniting IDP with chronic inflammatory diseases of visceral of different localization. The objective of the study was identification of metabolic factors of pathogenetic community of GIDP and a comorbid chronic focal infection of different localization. Material and methods. The activity of systemic factors of inflammation were studied in the patients with generalized periodontitis (GP) of developed stage on a background of multiple chronic foci of infection: level and ratios of pro- and antiinflammatory cytokines – interleukins 2,6,10, TNF-α, C – reactive protein in comparison with the activity of oxidation of lipids, proteins, low molecular weight thiols, assessment of levels of Zn, Cu, Fe in biological environments and the hepsidin blood level. Results and discussion. Significantly more expressed metabolic disorders in comorbidity multiple chronic foci of infection and GP, than in the absence of periodontium lesions have been shown. Increased lipid peroxidation and free radical oxidation of thiols (p<0.01), increased levels of C – reactive protein level and pro-inflammatory cytokines (TNF-α, IL 6), and imbalance in the distribution of such trace elements as copper, zinc, iron in environments of organism were found in patients with combined pathology of comorbidity multiple chronic foci of infection and GP. Conclusions. Thus, the findings of the study demonstrate that formation of multiple chronic foci of infection in an organism is connected with increase of mediators of system inflammation in blood, disorders of redox metabolism and deficiency of such trace elements as Cu, Zn, Fe which are the key factors of a enzyme link of antioxidant protection.